Auditorium of the future: e learning platform - BATIREL, HASAN FEVZİ (AME PUBL CO, 2021)
Principles of surgical training have not changed, but methods of training are evolving very fast. Online tools are being adopted in both knowledge and skills training for surgical residents. As a result, to evaluate the outcome of these tools, online assessment is also developing. Knowledge resources are very diverse ranging from lectures, webinars, surgical videos to three-dimensional planning and printing. Skills resources include virtual reality simulators, remote skills training and interdisciplinary teamwork. Assessment of E-learning tools can be performed using online questions, task-based simulations, branching scenarios and online interviews/discussions. In thoracic surgery, video assisted thoracic surgery (VATS) lobectomy simulator has been developed and it appears to be an important tool for minimally invasive thoracic surgery education. Training programs incorporate e-Learning in their curriculum and online training and assessment will become an important part of thoracic surgical training as well.
Keywords: E-learning; surgical education; simulation; assessment